Preparation of endometrium for frozen embryo transfer cycles - Yana A. Petrosyan; Anastasiya G. Syrkasheva; Andrey Yu. Romanov; Nataliya P. Makarova; Elena A. Kalinina (Гинекология, 2020)
Aim. Aim of the study was to the effectiveness of various endometrial preparation protocols in IVF frozen embryo transfer cycles.